Retinal Microvasculature Changes in Patients With Coronary Total Occlusion on Optical Coherence Tomography Angiography - Zhong, Pingting; Hu, Yijun; Jiang, Lei; Peng, Qingsheng; Huang, Manqing; Li, Cong; Kuang, Yu; Tan, Ning; Yu, Honghua; Yang, Xiaohong (Frontiers in Medicine, 2021)
Background: Retinal microvasculature has been associated with coronary artery disease (CAD), but the exact contributory role in coronary total occlusion (CTO) is unclear. We aimed to investigate whether retinal vasculature is associated with CTO and could provide incremental value in the assessment of CTO. Methods: A total of 218 CAD patients including 102 CTO and 116 non-CTO were enrolled. Retinal vasculature was measured by optical coherence tomography angiography (OCTA) for all patients. Receiver operating characteristic (ROC) curve was used to assess the performance of retinal vasculature in differentiating CTO from non-CTO patients. Results: In non-CTO CAD patients, vessel density (VD) of mean superficial capillary plexus (SCP) and parafovea SCP were 49.85 and 52.56%, respectively; in CTO patients, VD of mean SCP and parafovea SCP were 47.77, and 49.58%, respectively. After multiple adjustment, VD in the SCP was significantly lower in CTO patients compared to non-CTO patients. VD of superior hemi in the parafovea SCP combined with the clinical variates showed the best ability to predict CTO from CAD with an area under the curve (AUC) of 0.812 (specificity of 89.0% and sensitivity of 65.9%). Conclusions: In CTO patients, retinal VD was significantly decreased, and microvascular damage might specifically target to arterioles than capillaries. Retinal vasculature could thus be a surrogate for detecting the microvascular damage and assist in the assessment of CTO patients. OCTA examination could be suggested to monitor the process of coronary arteries lesions.